THE EFFECTIVENESS OF TEACHING WRITING TO THE STUDENTS WITH THE TECHNIQUE “REWARDS AND POSITIVE REINFORCEMENT” (Academicia Globe: Inderscience Research, 2023)
The article shows the effectiveness of teaching writing with the technique “Rewards and positive reinforcement”. Based on “rewards and positive reinforcement” to the students and improved writing skills of students a general conclusion has been made about the effectiveness of the technique for developing future English teachers’ writing skills.